The Role of Cytokines and Chemokines in Shaping the Immune Microenvironment of Glioblastoma: Implications for Immunotherapy - Yeo, Erica C. F. (Cells, 2021)
Glioblastoma is the most common form of primary brain tumour in adults. For more than a decade, conventional treatment has produced a relatively modest improvement in the overall survival of glioblastoma patients. The immunosuppressive mechanisms employed by neoplastic and non-neoplastic cells within the tumour can limit treatment efficacy, and this can include the secretion of immunosuppressive cytokines and chemokines. These factors can play a significant role in immune modulation, thus disabling anti-tumour responses and contributing to tumour progression. Here, we review the complex interplay between populations of immune and tumour cells together with defined contributions by key cytokines and chemokines to these intercellular interactions. Understanding how these tumour-derived factors facilitate the crosstalk between cells may identify molecular candidates for potential immunotherapeutic targeting, which may enable better tumour control and improved patient survival.